Understanding of the BESIII measurement of (anti)hyperon-nucleon scattering - Xiao-Yun Wang; Yuan Gao; Xiang Liu (Physics Letters B, 2025)
Focusing on the recent measurements of the scattering processes Λ¯p→Λ¯p and Λp→Λp reported by BESIII, we offer a dynamical interpretation of the differences in the measured total and differential cross sections for both processes. This discrepancy arises because the u-channel contribution is forbidden for Λ¯p→Λ¯p but allowed for Λp→Λp. Additionally, we examine the enhancement effect in the forward angle region of the differential cross section for Λ¯p elastic scattering, attributed to the t-channel contribution. This work serves as a test to the scattering mechanism involved in these reactions.